CYBERSECURITY LAW AND LEGAL RESPONSES TO DATA BREACHES IN GOVERNMENT INSTITUTIONS - Yeni Santi; Rahmatiyah Rahmatiyah; Agus Prasetyo (CV. Lafadz Jaya, 2026)
This study aims to analyze the cybersecurity legal framework and legal responses to data breach incidents in government institutions. As the digitalization of public services increases, threats to data security are becoming increasingly complex and have a broad impact on public trust and the stability of state administration. The method used in this study is a literature review, examining various academic sources, regulations, and policy reports related to cybersecurity and data protection in the public sector. This approach allows for the identification of regulatory patterns, legal weaknesses, and best practices in handling data breaches across various jurisdictions. The results of the study indicate that although many countries have developed regulations related to cybersecurity and data protection, gaps remain in their implementation, inter-agency coordination, and law enforcement mechanisms. Legal responses to data breaches in government institutions are often reactive and do not fully prioritize the principles of prevention and risk mitigation. Furthermore, the lack of uniform security standards and limited human resources are major challenges in strengthening government information security systems. Therefore, this study emphasizes the importance of regulatory harmonization, institutional capacity building, and the adoption of a proactive approach to cyber risk management to improve the effectiveness of data protection in the public sector.